Live-work planning and design : zero-commute housing - Dolan, Thomas (Hoboken, New Jersey : John Wiley & Son, Inc., 2012)
Although the live-work concept is now accepted among progressive urban design and planning professionals, the specifics that define the term, and its application, remain sketchy. This encyclopedic work is sure to change that, providing the critical information that is needed by architects, planners and citizens.
Preface -- Acknowledgments -- 1. Introduction: A Brief History and Description of Live-Work -- 2. Defining Live-Work -- 3. Designing live-work: meeting its unique needs -- 4. The market for live-work -- 5. Live-work and community: a natural marriage -- 6. Live-work planning issues and regulatory solutions -- 7. Live-work building code issues -- 8. Epilogue -- Appendix A: Toward a model live-work planning code -- Appendix B: Model live-work building code system -- Appendix C: Live-work resources -- Endnotes -- Index.
Includes bibliographical references and index.
Keywords: MULTIPURPOSE BUILDINGS